INTEGRASI PENDIDIKAN BERWAWASAN LINGKUNGAN HIDUP (GREEN SCHOOL) MELALUI PEMBELAJARAN PAI DI SEKOLAH - Ahsan Muzadi; Siti Mutholingah (Ta`Limuna: Jurnal Pendidikan Islam, 2019)
The era of globalization which is characterized by increasingly sophisticated technological developments not only brings positive impacts but also brings negative impacts, one of which is global warming or global warming. Global warming is increasingly unavoidable, especially due to human activity. Human activities that use technology excessively and unwise and do not pay attention to environmental sustainability are the main factors causing global warming. This is very contrary to the teachings of Islam which always teaches to always preserve the environment. Islamic Religious Education in schools has a role in participating in realizing education that is environmentally sound or often known as green school. This study aims to analyze the concept of Green Insights and to find the concept of integration of Green Insights in the learning of Islamic Education in schools. This research takes the form of library research or literature review of existing references. The results of this study are 1) Islamic Education in schools in this case aims to realize human beings who play a role as khalifatullah, which has a very important role in realizing environmental education (green school). 2) The concept of integration of Green Insights through PAI learning consists of 4 forms, namely (a) Integration through PAI's intracuricular activities, (b) Integration through PAI's curricular activities, (c) Integration through PAI's extracurricular activities, (d) Integration through PAI's non-curricular activities (the formation of ecology or green school culture).